Stupa in Cave 10 at Kondivate - Temples of India Project Team (Jio Institute, 2024)
The worship of the living ascetic, a tradition deeply rooted in Indian culture, influenced early temple architecture. Cave 10 at Kondivate, where the Buddha is represented by a stupa, and housed inside a likeness of a hut in stone.